Influence of increasing chromium content on additively manufactured tool steels: Microstructural and mechanical evolution before and after heat treatment - Nicole Ofner; Sabine Carmen Bodner; Peter Kunnas; Atacan Asci; Kevin Kutleša; Andreas Stark; Philipp Höbenreich; Christin Aumayr; Liang Wu; Christoph Turk; Jozef Keckes; Michael Meindlhumer (Journal of Materials Research and Technology)
The demand for high performance materials and tailored alloys is increasing within the additive manufacturing (AM) community. Therefore, this study investigates and explores the influence of increasing Cr content on the microstructure and mechanical properties of martensitic tool steels suitable for AM processing. The analysis covers both the as-built (AB) and heat-treated (HT) conditions, where the latter includes austenitization, quenching and multiple tempering steps. Thus, three Cr-alloyed tool steels, named Alloy A (20 wt% Cr), Alloy B (22 wt% Cr), and Alloy C (24 wt% Cr), were analyzed in the AB and HT conditions. Comprehensive microstructural characterization techniques, including optical microscopy, scanning electron microscopy, electron backscatter diffraction, and transmission electron microscopy unveiled a clear correlation between the Cr content and the resulting microstructural features and phase occurrences. An in situ synchrotron experiment identified the body-centered cubic-Fe phase in the alloys exclusively as δ-ferrite. Increasing the Cr content resulted in a higher amount of δ-ferrite in both the AB and HT conditions, which consequently reduced the amount of martensite after heat treatment. Mechanical properties, evaluated through Vickers hardness and tensile testing, revealed a decrease in hardness and tensile strength accompanied by a change of the deformation behavior from brittle to ductile with increasing Cr content and consequently increased δ-ferrite content. This study thus contributes to a deeper understanding of the effects of increasing Cr content on the microstructural characteristics, phase occurrence and mechanical properties of high Cr-alloyed tool steels produced via additive manufacturing.